On Round Table Session of VI International Contest “Sibiriada” (December 9, 2017, Myski, Kemerovo region) - N. D. Ulturgasheva; S. V. Serebrennikov; O. A. Tsukanova (Научный диалог)
The results of the “round table” held on December 9, 2017 in Myski, Kemerovo region within the framework of the VI International Competition “Sibiriada” are presented. The round table was devoted to actual problems of protection of traditional culture, genres of musical creativity (song, instrumental), and also production of national musical instruments of indigenous peoples of the Sayano-Altay uplands and southern Siberia on the basis of modern technologies. The problem of grant support for research and projects aimed at the preservation of traditional cultures in national cultural centers, the study of unexplored issues of the history of indigenous peoples of Siberia was also discussed.